Active tectonics and palaeoseismicity of the Northern Tien Shan and Dzhungaria - Tsai, C-H (2023)
This thesis focuses on the active tectonics and the palaeoseismicity around the Dzhungarian Basin. The study of surface ruptures is crucial to comprehending the earthquake occurrences of faults. I investigate geomorphic displacements along the boundary strike-slip Dzhungarian Fault using high-resolution drone and Pléiades satellite imagery. The results reveal possible single-event fault slip along the Dzhungarian Fault in the most recent earthquake. I suggest this earthquake is likely linked with a previously identified palaeo-earthquake rupture on the Lepsy Fault. With a joint rupture of the two faults, it could generate an earthquake with a magnitude up to Mw 8.4, which would be amongst the largest magnitude inferred for a continental earthquake. I further use Quaternary dating techniques and InSAR time-series analysis to determine the geological and geodetic slip rates of the Dzhungarian Fault. The results show that the northern Dzhungarian Fault has a long-term uplift rate of 0.6 ± 0.2 mm/yr, whilst the southern Dzhungarian Fault has geological and geodetic strike-slip rates consistent with a range of 2.1 – 4.7 mm/yr. I also re-investigate three historical earthquakes with magnitudes greater than Mw 7.0: the 1812 Nilke, the 1906 Manas and the 1944 Xinyuan Earthquakes in the Borohoro Shan. By re-analysing source parameters and integrating published data, seismological analysis results, and remote-sensing mapping, the study demonstrates the significance of both reverse and strike-slip faulting in the regional seismotectonics, which also indicates the deformation kinematics of the Borohoro Shan as being in a transpressional zone. I collate my results with those from the literature to propose updated earthquake scaling relationships of intra-continental earthquakes. Finally, this study suggests that the Dzhungarian Basin and its surrounding tectonic units are rotating anticlockwise to accommodate both the N-S crustal shortening and the left-lateral shearing within a large-scale zone from the SW Tien Shan to the Altay Mountains.